Prognostic Factors for Drop Foot Due to Lumbar Degenerative Diseases: The Impact of Surgical Timing on Postoperative Recovery. Issue 4 (May 2020) - Masuda, Soichiro; Kanba, Yusuke; Kawai, Jun; Ikeda, Noboru
Abstract : Study Design: Retrospective clinical series. Objective: To investigate the prognostic factors for the improvement of drop foot caused by degenerative lumbar disease after surgery. Summary of Background Data: Drop foot may be caused by lumbar spinal diseases and may affect daily life. There are limited data regarding predictors of drop foot, especially surgical timing. Methods: We retrospectively reviewed data from 87 patients with drop foot. Prognostic factors and precise timing of surgery affecting drop foot improvement were examined by multivariate logistic regression analysis. Results: Forty patients (46.0%) recovered from drop foot after surgery. Age [odds ratio (OR)=0.93; 95% confidence interval (CI), 0.87−0.98; P =0.01], preoperative anterior tibialis muscle strength (OR=12.0; 95% CI, 2.41−59.9; P =0.002), and duration of drop foot before surgery (OR=3.59; 95% CI, 1.09−11.8; P =0.04) were significant prognostic factors. Two months was the most appropriate cutoff for surgery after appearance of symptoms. Conclusions: Age, preoperative tibialis anterior muscle strength, and duration of drop foot were statistically significant prognostic factors of recovery from drop foot. Surgery within 2 months after the onset of drop foot may improve postoperative outcome.